A diversity of SERCA Ca2+ pump inhibitors. (20th May 2011) - Michelangeli, Francesco; East, J. Malcolm
Abstract : The SERCA (sarcoplasmic/endoplasmic reticulum Ca 2+ -ATPase) is probably the most extensively studied membrane protein transporter. There is a vast array of diverse inhibitors for the Ca 2+ pump, and many have proved significant in helping to elucidate both the mechanism of transport and gaining conformational structures. Some SERCA inhibitors such as thapsigargin have been used extensively as pharmacological tools to probe the roles of Ca 2+ stores in Ca 2+ signalling processes. Furthermore, some inhibitors have been implicated in the cause of diseases associated with endocrine disruption by environmental pollutants, whereas others are being developed as potential anticancer agents. The present review therefore aims to highlight some of the wide range of chemically diverse inhibitors that are known, their mechanisms of action and their binding location on the Ca 2+ ATPase. Additionally, some ideas for the future development of more useful isoform-specific inhibitors and anticancer drugs are presented.